“Global Precariat“? Unequal and Combined Informalization as a challenge for research and political action - Bach, Bert; Blaha, Karola (Momentum Quarterly, 2019)
In their contribution, Bach/Blaha attempt to classify precarious employment relationships globally in conceptual and empirical terms. The starting point is the precarization debate, which has been conducted more intensively since the 1990s and refers to institutional contexts of the global North. With reference to the discussion on informal employment and informalization in the global South, which goes back some time and focuses on broader, more diverse phenomena, the authors prefer the term informalization as a superordinate, globally usable or less context-dependent term in order to grasp phenomena of insecurity and vulnerability as well as connections between formal and informal employment segments, for example within the framework of transnational value chains. Against the background of very limited data, this paper attempts to quantify different forms of employment in a global context in order to approach a global class structure. The second part of the article follows on from these empirical findings and examines challenges for the organisation and articulation of interests of informal workers and subaltern workers in general. With reference to power resource approaches, considerations are made about opportunities and barriers of organizing.